Negotiation Processes of "Pentecostal" and "Evangelical" Identity in Costa Rica. (17th April 2019) - Kurzewitz, Nora
Abstract : Pentecostal identity in Costa Rica is determined by its relationship to Catholicism. Those who currently are referred to as "Pentecostal" refer to themselves as "Evangelical" or as "Christian". Thus they distinguish themselves from Catholics, whom they pejoratively call "religious". This boundary creates a sense of identity for Evangelical Pentecostals and non-Pentecostals. At the same time, Evangelical Pentecostals are connected with Catholic Pentecostals in local history and present local discourse. Unravelling these complex name politics, this article illustrates how political dynamics on the local level along with their global entanglement shape Pentecostal self-understandings. It concludes that in order to study "Pentecostalism" adequately it is necessary not to operate with essentialist definitions but to contextualize it genealogically.